2020
DOI: 10.1177/8756087920926649
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline and quantum dot-based nanostructures: Developments and perspectives

Abstract: Quantum dots are 2–5 nm nanoparticles with exceptional optical, electronic, luminescence, and semiconducting properties. Polyaniline is an exclusive conjugated polymer. This article reviews recent efforts, scientific trials, and technological solicitations of the polyaniline/quantum dot-based nanocomposites. Polyaniline/quantum dot mixtures form a unique composition for advance materials and applications. Carbon dots, graphene quantum dots, and several inorganic quantum dots have been added to a conducting pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Electrothermal responses have also been explored to realize SME in polymers. SMP nanocomposites based on nanoinclusions including graphene396,397 self‐assembled silver nanowires,398 carbon nanofibers,399 siloxane‐modified alumina powders with carbon fibers,400 nanoporous gold,401 and CNTs402,403 enable electrothermal deformation and shape programming. Similarly, including carbon black in polymeric materials is a facile route to enabling either photothermal or electrothermal responses 404.…”
Section: Shape Memory Polymersmentioning
confidence: 99%
“…Electrothermal responses have also been explored to realize SME in polymers. SMP nanocomposites based on nanoinclusions including graphene396,397 self‐assembled silver nanowires,398 carbon nanofibers,399 siloxane‐modified alumina powders with carbon fibers,400 nanoporous gold,401 and CNTs402,403 enable electrothermal deformation and shape programming. Similarly, including carbon black in polymeric materials is a facile route to enabling either photothermal or electrothermal responses 404.…”
Section: Shape Memory Polymersmentioning
confidence: 99%
“…Composites of PANI with quantum dots of various carbonaceous materials have been reviewed, but very few examples of tests as supercapacitor electrodes were mentioned [ 187 ]; for further examples, see [ 188 , 189 , 190 ]. In the latter case, the gravimetric storage capability of the composite increased by a factor of five at the optimum composition (10 wt.% quantum dots), 80% of the initial capacitance were left after 3000 cycles.…”
Section: The Combinationsmentioning
confidence: 99%
“…The electrospinning technique uses an electrostatic force (direct current) of several kV to generate fibers of the nanocomposite from a solution or melt. 125 Mike Tebyetekerwa et al reported polyindole/carbon nanotube (PIN/CNT) nanofibers fabricated via the electrospinning process for the first time. 126 In the procedure, a little percentage of CNTs were introduced into the spinning solution containing PIN and PEO.…”
Section: Review Materials Advancesmentioning
confidence: 99%